2019
DOI: 10.1186/s12903-019-0792-7
|View full text |Cite
|
Sign up to set email alerts
|

Trueness and precision of 5 intraoral scanners in the impressions of single and multiple implants: a comparative in vitro study

Abstract: Background Until now, a few studies have addressed the accuracy of intraoral scanners (IOSs) in implantology. Hence, the aim of this in vitro study was to assess the accuracy of 5 different IOSs in the impressions of single and multiple implants, and to compare them. Methods Plaster models were prepared, representative of a partially edentulous maxilla (PEM) to be restored with a single crown (SC) and a partial prosthesis (PP), and a totally edentulous maxilla (TEM) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
226
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(260 citation statements)
references
References 35 publications
25
226
1
8
Order By: Relevance
“…As this was an edentulous case, some problems had to be managed: few studies support the use of IOSs for impression capture on multiple implants aimed at the manufacture of extended implant-supported restorations as full arches. This limitation is determined by the acquisition methods of IOS and the difficulty of reconstructing extended surfaces [22]. In addition, obtaining accurate digital scans of the arch where there are large homogeneous areas, such as the spaces between implants in edentulous arches, is especially difficult.…”
Section: Case Descriptionmentioning
confidence: 99%
“…As this was an edentulous case, some problems had to be managed: few studies support the use of IOSs for impression capture on multiple implants aimed at the manufacture of extended implant-supported restorations as full arches. This limitation is determined by the acquisition methods of IOS and the difficulty of reconstructing extended surfaces [22]. In addition, obtaining accurate digital scans of the arch where there are large homogeneous areas, such as the spaces between implants in edentulous arches, is especially difficult.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The Distance between them is Measured (21) It was observed that no difference was found in the intra oral simulators. However, the scanners showed deviations at D6 AND the accuracy was highest in TRIOS, followed by Identica Blue and deviations were more in Carestream (19) .…”
Section: Figure 1 Specific Points D3 D6 and D7 On The Modelmentioning
confidence: 99%
“…It was concluded that CS3600 displayed the highest trueness and precision among the 5 scanners followed by TRIOS, DWIO, Omnicam and Emerald sequentially. (21) Although differences in the accuracy between different scanners were present, they were not taken into account in this study.…”
Section: Figure 1 Specific Points D3 D6 and D7 On The Modelmentioning
confidence: 99%
“…With the advent of digital technology, a new era in dentistry has begun [25]. From acquisition methods such as cone beam computed tomography (CBCT), which have considerably reduced the number of x-rays given to patients [26], to intraoral scanners [27], digital software, 3D printers and many other methods and materials [28], these technologies have simplified, improved and substantially sped up several procedures. Such technological advancement allows clinicians to see the world of dentistry in a completely different way, which is developing exponentially [25].…”
Section: Introductionmentioning
confidence: 99%